2021
DOI: 10.3389/fcvm.2021.640124
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Monocyte Subsets and Cardiometabolic Disorders/Cardiovascular Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Monocyte subsets in humans, i.e., classical (CM), intermediate (IM), and non-classical monocytes (NCM), are thought to differentially contribute to the pathogenesis of atherosclerosis, the leading cause of cardiovascular disease (CVD). However, the association between monocyte subsets and cardiometabolic disorders and CVD is not well-understood. Thus, the aim of the current systematic review and meta-analysis was to evaluate recent findings from clinical studies that examined the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 83 publications
1
22
0
Order By: Relevance
“…Human monocytes are a heterogeneous cell population in the circulation and are classified as classical (CD14 ++ CD16 -), intermediate (CD14 ++ CD16 + ), and non-classical (CD14 + CD16 ++ ) monocytes 28 , which contribute differently to inflammatory responses and CVD development 29 . Notably, a systematic review and meta-analysis reported there may be a shift in the distribution of monocyte subsets from classical towards intermediate and/or non-classical monocytes in individuals at cardiovascular risk as compared to healthy controls 30 . In individuals with CKD, the proportion of the intermediate monocytes, known to be highly pro-inflammatory 31 , are expanded as compared to those without CKD 32,33 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Human monocytes are a heterogeneous cell population in the circulation and are classified as classical (CD14 ++ CD16 -), intermediate (CD14 ++ CD16 + ), and non-classical (CD14 + CD16 ++ ) monocytes 28 , which contribute differently to inflammatory responses and CVD development 29 . Notably, a systematic review and meta-analysis reported there may be a shift in the distribution of monocyte subsets from classical towards intermediate and/or non-classical monocytes in individuals at cardiovascular risk as compared to healthy controls 30 . In individuals with CKD, the proportion of the intermediate monocytes, known to be highly pro-inflammatory 31 , are expanded as compared to those without CKD 32,33 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes are white blood cells derived from bone marrow, with the ability to differentiate into macrophages and dendritic cells, and their adhesion to the damaged endothelium is a hallmark of atherosclerotic lesions in its early stages. Ox-LDL stimulates monocytes circulating in the blood to migrate towards the arterial wall [ 42 , 43 , 44 , 45 ]. Circulating monocytes are present in three forms based on the levels of cluster of differentiation (CD)14 and CD16 expression (surface cell protein markers): classical monocytes (approx.…”
Section: Monocytesmentioning
confidence: 99%
“…Functionally distinct monocyte subsets play different roles in the pathogenesis of cardiovascular disease 22 , but their implications in hypertension in pregnancy are unclear. Women with prior hypertension in pregnancy have altered cardiovascular adaptation to pregnancy, which may be related to increased proinflammatory monocytes and lead to the development of recurrent hypertension.…”
Section: Introductionmentioning
confidence: 99%